146k views
1 vote
Question 19 of 20 Use the quadratic formula to find the solutions to the equation. x2-3x+1 = 0 A. 3+ 15 4 B. 30.5 2 O c. 21./24 c 2 O.D. 51 V10 3 KUBMIT

User Kark
by
5.4k points

1 Answer

7 votes

The standard form of a quadratic equation is expressed as

ax^2 + bx + c = 0

The given equation is

x^2 - 3x + 1 = 0

By comparing the equation with the standard equation, we have

a = 1, b = - 3, c = 1

The quadratic formula is expressed as


\begin{gathered} x\text{ = }\frac{-\text{ b}\pm\sqrt[]{b^2-4ac}}{2a} \\ \text{Substituting the given values into the formula, } \\ x\text{ = }\frac{-\text{ - 3}\pm\sqrt[]{-3^2-4(1*1)}}{2*1} \\ x\text{ = }\frac{3\pm\sqrt[]{9\text{ - 4}}}{2}\text{ or }\frac{3\pm\sqrt[]{5}}{2} \end{gathered}
x\text{ = }\frac{3+\sqrt[]{5}}{2}\text{ or x = }\frac{3-\sqrt[]{5}}{2}

User Bram Gerritsen
by
4.8k points